A Novel Immunochromatographic Strip Based on Latex Microspheres for the Rapid Detection of North American-Type Porcine Reproductive and Respiratory Syndrome Virus - Li, Wansheng; Li, Minhua; Zhang, Hongliang; Li, Chao; Xu, Hu; Gong, Bangjun; Fu, Jun; Guo, Zhenyang; Peng, Jinmei; Zhou, Guohui; Tian, Zhijun; Wang, Qian (Frontiers in Microbiology, 2022)
A latex microsphere-based immunochromatographic strip (ICS) test was successfully developed for the rapid and sensitive detection of porcine reproductive and respiratory syndrome virus (PRRSV). The PRRSV N protein-specific monoclonal antibody (mAb) 1H4 labeled with latex microspheres was dispensed on a conjugate pad for use as the detector. The same mAb and goat anti-mouse antibody were blotted on a nitrocellulose membrane to form test and control lines, respectively. The limit of virus detection was approximately 5×102.0 median tissue culture infectious dose (TCID50)/mL. The limit of N protein detection was approximately 15 ng/mL. Other common porcine viruses were tested to evaluate the specificity of the ICS, and positive results were observed for only North American-Type PRRSV. A comparison of the strip with a standard diagnostic test (reverse transcriptase polymerase chain reaction, RT-PCR) was also performed. The ICS test was shown to be of relative high specificity and sensitivity, 90.32% and 73.91%, respectively. These results suggest that the ICS test can be used to quickly and accurately detect PRRSV and can be suitable for diagnostic purposes in the field.